Pengembangan Model Pembelajaran Berbasis LMS Gamifikasi Bermuatan TPACK dalam Materi Pembuatan Game Edukasi untuk Mengakselerasi Literasi Teknologi dan Pedagogi Mahasiswa PPG Seni Budaya - Ike Ratnawati; Dwi Sulistyorini; Mitra Istiar Wardhana; Maria Goretti Indah Della Conseta; Muslim; Ira Junita Suryantoro (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to develop a learning model based on Learning Management System (LMS) that is integrated with gamification strategies and TPACK (Technological Pedagogical Content Knowledge) content to be used in making educational games for students of the Teacher Professional Education Program (PPG) of Cultural Arts. The main goal of this development is to accelerate students' technological literacy and pedagogy to be able to design and produce educational games that are relevant to the context of art learning. The model was developed using the Research and Development (R&D) approach with the ADDIE model, but only focused on the initial three stages, namely Analysis, Design, and Development. The analysis stage was carried out to identify learning needs and map the level of digital literacy and pedagogic of students. The design stage includes designing the learning model structure, gamification elements, and TPACK-based content integration. While the development stage involves the creation of a gamified LMS prototype and validation tests by subject matter experts, media experts, and limited users. The results of the development show that t(Prasetyo dkk., 2024)his learning model is feasible to be implemented and received a positive response from PPG Arts and Culture students. The resulting model not only enriches the digital learning experience, but also improves students' ability to design educational games based on art and culture in a contextual and technology-integrated manner.